Risk, networks and privateering in Liverpool during the Seven Years War, 1756-1763 - Haggerty, Sheryllynne (SAGE Publications, 2018)
Privateering has often been portrayed as a particularly risky business. Some historians have posited that it was undertaken only by disreputable merchants, whilst others have argued that profits would not have been made if systems of control had been absent, and that merchants were in fact rational when they invested in privateering. So far, however, no-one has sought to gauge or measure the perceived riskiness of privateering by the merchants themselves, and the rationality of those who participated in it. Using the Seven Years War as a case study, this article seeks to measure the extent to which Liverpool merchants perceived privateering to be a risky proposition. As a measurement of the perception of risk, the network size in Liverpool’s privateering voyages is compared to those in the Liverpool slave trade, another trade known to be risky, but one in which Liverpool merchants excelled. In the case of ‘private men of war’, the network size was usually at least as large as those in the slave trade, and often larger. Therefore, the analysis presented here demonstrates that Liverpool’s merchants did perceive privateering—especially its ‘deep water’ variant—as a particularly risky activity during the Seven Years War. By their use of their networks, however, through which they both spread risk, and brought in wider financial and human capital, they were essentially rational in their pursuit of this particular business.